STRATEGI PEMASARAN BERBASIS MARKETING MIX DALAM MENSTABILKAN KONTINUITAS PELANGGAN PADA UMKM LANCAR JAYA WALLETCRAFT - Awaliya Franciska, Cahya; Munawaroh, Siti (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the marketing mix based strategies used to stabilize customer continuity at Lancar Jaya Walletcraft. The research employs a descriptive qualitative approach with data collected through interviews, observations, and documentation. Informants consisted of the business owner and several wholesale customers. Findings indicate that the marketing mix plays a crucial role in maintaining customer continuity: product strategies emphasize customization, material quality, neat stitching, and quality control. pricing is set based on production costs with adjustments to remain competitive, distribution operates through business-to-business relations and personal selling, promotion is conducted via WhatsApp and supported by after-sales service. The study concludes that consistent application of the marketing mix, supported by product quality consistency and strong customer relationships, enhances customer satisfaction and encourages sustainable repeat purchases.